Electrical Structure of the Lithosphere From Rio de la Plata Craton to Paraná Basin: Amalgamation of Cratonic and Refertilized Lithospheres in SW Gondwanaland - Bologna, M. S. (2018)
We conducted a magnetotelluric (MT) study from Paleoproterozoic Rio de la Plata Craton, in Uruguay, toward Paleozoic-Mesozoic Paraná Basin, in Brazil. The 850-km-long MT transect comprises 35 evenly spaced broadband electromagnetic soundings sites. In the Paraná Basin, 11 additional long-period measurements were acquired to extend the maximum depth of investigation. All data were inverted using two- and three-dimensional approaches obtaining the electrical resistivity structure from the surface down to 200 km. The Rio de la Plata Craton is >200-km thick and resistive (~2,000 Ωm). Its northern limit is electrically defined by a lithosphere scale lateral transition and lower crust conductive anomalies (1–10 Ωm) interpreted as a Paleoproterozoic suture at the southern edge of Rivera-Taquarembó Block. The latter is characterized by an approximately 100-km thick and moderate resistive (>500 Ωm) upper mantle. The Ibaré shear zone is another suture where an ocean-ocean subduction generated the 120-km thick and resistive (>1,000 Ωm) São Gabriel juvenile arc. Proceeding northward, a 70- to 80-km thick, 150-km wide, and inclined resistive zone is imaged. This zone could be remnant of an oceanic lithosphere or island arcs accreted at the southern border of Paraná Basin. The MT transect terminates within the southern Paraná Basin where a 150- to 200-km-thick less resistive lithosphere (<1,000 Ωm) may indicate refertilization processes during plate subduction and ocean closure in Neoproterozoic-Cambrian time. Our MT data support a tectonic model of NNE–SSW convergence for this segment of SW Gondwanaland.